Electro-thermal peltier cooling system for internal combustion engine waste heat recovery - Raja, Selvakumar; John, Bilu P.; Nandagopal, Sasikumar; Palani, Loganathan; Elumalai, Sangeethkumar; Velmurugan, Ramanathan; Kumar, Aman; Neelamana, Hrishikesh Kizhakkillam (AIP conference proceedings, 2024)
The loss of heat energy from the Internal Combustion Engines are more as compared with the other energy systems. To avoid or utilization of the heat sources are important. In other hand development of semiconductors and the incorporation of the thermoelectric devices are mostly used to avoid the above mentioned statement. In this work the peltier cooling system has been the subject of major advances in recent years and peltier element for CPU cooling, refrigeration, temperature stabilization for peltier cooling with direct energy conversation of heat (thermoelectric generators driven by waste heat, radioactive decay, combustion). In this project, we proposed and built a Peltier-based automatic engine cooling system, which has superior conduction as well as convection thermal characteristics compared to a radiator system. The recommended thermoelectric cooler may replace conventional radiators without requiring additional mechanical components, except for the fundamental elements of the radiator’s legacy water-cooling system. They have no sound or vibration and are trustworthy energy converters. In addition to being lightweight and tiny, they also provide more accurate temperature control. The engine’s temperature is kept between 18°C and 45°C in this experiment using a Peltier element, temperature sensor, micro-controller, relays, and arduino controller. The typical surface temperature of a central heating radiator in use today ranges from 60 to 90 degrees Celsius, and natural convection contributes more to overall heat transmission than radiative transfer. The use of a thermoelectric cooler (TEC) to increase the heat transfer from the engines to the surrounding air is examined in this research.